Collection management and study of microscope slides: Storage, profiling, deterioration, restoration procedures, and general recommendations - Neuhaus, Birger; Schmid, Thomas; Riedel, Jens (Zootaxa, 2017)
A wide range of aspects concerning microscope slides, their preparation, long-time storage, curatorial measures in collections, deterioration, restoration, and study is summarized based on our own data and by analyzing more than 600 references from the 19th century until 2016, 15 patents, and about 100 Materials Safety Data Sheets. Information from systematic zoology, conservation sciences, chemistry, forensic sciences, pathology, paleopathology, applied sciences like food industry, and most recent advances in digital imaging are put together in order to obtain a better understanding of which and possibly why mounting media and coverslip seals deteriorate, how slides can be salvaged, which studies may be necessary to identify a range of ideal mounting media, and how microscope studies can benefit from improvements in developmental biology and related fields. We also elaborate on confusing usage of concepts like that of maceration and of clearing. The chemical ingredients of a range of mounting media and coverslip seals are identified as much as possible from published data, but this information suffers in so far as the composition of a medium is often proprietary of the manufacturer and may vary over time. Advantages, disadvantages, and signs of deterioration are documented extensively for these media both from references and from our own observations. It turns out that many media degrade within a few years, or decades at the latest, except Canada balsam with a documented life-time of 150 years, Euparal with a documented life-time of 50 years, and glycerol-paraffin mounts sealed with Glyceel, which represents almost the only non-deteriorating and easily reversible mount. Deterioration reveals itself as a yellowing in natural resins and as cracking, crystallization, shrinkage on drying or possibly on loss of a plasticizer, detachment of the coverslip, segregation of the ingredients in synthetic polymers, as well as continued maceration of a specimen to a degree that the specimen virtually disappears. Confusingly, decay does not always appear equally within a collection of slides mounted at the same time in the same medium. The reasons for the deteriorative processes have been discussed but are controversial especially for gum-chloral media. Comparing data from conservation sciences, chemical handbooks, and documented ingredients, we discuss here how far chemical and physical deterioration probably are inherent to many media and are caused by the chemical and physical properties of their components and by chemicals dragged along from previous preparation steps like fixation, chemical maceration, and physical clearing. Some recipes even contain a macerating agent, which proceeds with its destructive work. We provide permeability data for oxygen and water vapor of several polymers contained in mounting media and coverslip seals. Calculation of the penetration rate of moisture in one example reveals that water molecules reach a specimen within a few days up to about a month; this lays to rest extensive discussions about the permanent protection of a mounted specimen by a mounting medium and a coverslip seal. Based on the ever growing evidence of the unsuitable composition and application of many, and possibly almost all, mounting media, we strongly encourage changing the perspective on microscope slides from immediate usability and convenience of preparation towards durability and reversibility, concepts taken from conservation sciences. Such a change has already been suggested by Upton (1993) more than 20 years ago for gum-chloral media, but these media are still encouraged nowadays by scientists. Without a new perspective, taxonomic biology will certainly lose a large amount of its specimen basis for its research within the next few decades. Modern non-invasive techniques like Raman spectroscopy may help to identify mounting media and coverslip seals on a given slide as well as to understand ageing of the media. An outlook is given on potential future studies. In order to improve the situation of existing collections of microscope slides, we transfer concepts as per the Smithsonian Collections Standards and Profiling System, developed for insect collections more than 25 years ago, to collections of slides. We describe historical and current properties and usage of glass slides, coverslips, labels, and adhesives under conservational aspects. In addition, we summarize and argue from published and our own experimental information about restorative procedures, including re-hydration of dried-up specimens previously mounted in a fluid medium. Alternatives to microscope slides are considered. We also extract practical suggestions from the literature concerning microscope equipment, cleaning of optical surfaces, health risks of immersion oil, and recent improvements of temporary observation media especially in connection with new developments in digital software.